(3GdaUd aj Gdedd hGdfMds - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3GdMbjbI hCf cd gPG ehLhO ef GdUGdMjf Ydi SHjd GdcQGeI hEfg dG aQb Hjf BjGJ GdCfHjGA hHjf eG jXgQ ef GdEfSGf GdaGVd s
(3BNQgG (B:s
(3Je GdSaQ GdKGfi HJeGe LejY GdOjhGf ef GdaUd ai Gdedd hGdBQGA hGdfMd HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B319s
Keywords: (3GdJhMjO hGdedd hGdfMds